Low dose of sublingual immunotherapy in patients with allergic rhinitis in a randomized double-blind placebocontrolled study - Leal Villarreal, Lucía; Huerta López, José G.; Salinas Carmona, Mario César; Cárdenas Estrada, Eloy; Muñoz Espinosa, Linda Elsa; Castro Corona, María de los Ángeles; Medina de la Garza, Carlos Eduardo (Elsevier, 2010)
Background: Few placebo controlled studies for sublingual immunotherapy (SLIT) have been performed so far in Latin America, and some issues like treatment scheme and doses remain uncertain Objective: to asses improvement in nasal, pharyngeal and ocular symptoms with low doses of SLIT to Dermatophagoides pteronyssinus comparing it with a placebo, in a Mexican population with allergic rhinitis (AR). Methods: a prospective, double-blind placebo-controlled, randomized study, with 32, patients with chronic, moderate to severe AR; 16 patients were treated with SLIT and 16 with placebo for 6 months with a total dose of D. pteronyssinus (Der p1) of 50.4 mcg. Nasal, pharyngeal and ocular symptoms were monitored using a symptoms diary to evaluate the degree of improvement and reduction in the use of medication. Results: Significant lower symptom and drug scores were found in SLIT group where 85% of patients showed clinical improvement. On the placebo group, 24% of patients improved and 76% had no response or worsened; 94% of patients on SLIT required less symptomatic medication compared with the placebo group. There was a reduction in positivity to cutaneous test to D. pteronyssinus in 50% of the patients on SLIT, whereas placebo patients remained all positive